Significance of Biomarkers as a Predictive Factor for Post-Traumatic Sepsis - Kyung-Wuk Lee; Sung-Hyuk Choi; Young-Hoon Yoon; Jung-Youn Kim; Young-Duck Cho; Han-Jin Cho; Sung-Jun Park (Journal of Trauma and Injury)
Purpose Many traumatic patients die from sepsis and multiple organ failure. Early recognition of post-traumatic sepsis in traumatic patients will help improve the prognosis. Recently, procalcitonin (PCT), macrophage migration inhibitory factor (MIF), and lactic acid have emerged as predictive factors. Our study aims to explore the significance of PCT, MIF and lactic acid as a predictor of posttraumatic-sepsis in trauma patients. Methods This study was conducted on prospective observational study patients who visited an emergency medical center in a university hospital from March 2014 to February 2016. We measured the white blood cells, c-reactive protein (CRP), lactic acid, PCT, and MIF with serum taken from the patient’s blood within 1 hour of the occurrence of the trauma. The definition of post-traumatic sepsis was defined as being part of systemic inflammation response syndrome criteria with infections within a week. Results A total of 132 patients were analyzed, wherein 74 patients were included in the low injury severity score (ISS) group (ISS <15) and 58 patients were included in the high ISS group (ISS ≥15). The mean PCT, MIF, and lactic acid levels were higher in the high ISS group (p<0.05). Meanwhile, 38 patients were included in the early sepsis group and 94 patients were included in the non-sepsis group. The mean MIF levels were higher in the sepsis group than the non-sepsis group (p<0.05) and there were no significant differences in the initial CRP, lactic acid, and PCT levels in these two groups. Conclusions MIF may be considered as a predictive factor for sepsis in trauma patients.